2013
DOI: 10.1007/s12263-013-0362-6
|View full text |Cite
|
Sign up to set email alerts
|

ELOVL2 gene polymorphisms are associated with increases in plasma eicosapentaenoic and docosahexaenoic acid proportions after fish oil supplement

Abstract: Fish oil supplementation provides an inconsistent degree of protection from cardiovascular disease (CVD), which may be attributed to genetic variation. Single nucleotide polymorphisms (SNPs) in the elongation-ofvery-long-chain-fatty-acids-2 (ELOVL2) gene have been strongly associated with plasma proportions of n-3 longchain polyunsaturated fatty acids (LC-PUFA). We investigated the effect of genotype interaction with fish oil dosage on plasma n-3 LC-PUFA proportions in a parallel doubleblind controlled trial, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 32 publications
1
33
0
Order By: Relevance
“…SNPs in Elovl2, which encode elongases 2, have also been shown to alter longer chain PUFA status. Minor alleles of SNPs in Elovl2 have been associated with lower DHA [77] and EPA [78] status. In addition, a SNP in Elovl5 has been shown to be associated with lower capacity to convert EPA to DPA [91] .…”
Section: Genetic Influences On the Conversion Pathwaymentioning
confidence: 99%
“…SNPs in Elovl2, which encode elongases 2, have also been shown to alter longer chain PUFA status. Minor alleles of SNPs in Elovl2 have been associated with lower DHA [77] and EPA [78] status. In addition, a SNP in Elovl5 has been shown to be associated with lower capacity to convert EPA to DPA [91] .…”
Section: Genetic Influences On the Conversion Pathwaymentioning
confidence: 99%
“…These studies have shown strong associations between the minor allele carriers of single nucleotide polymorphisms (SNPs) within FADS gene cluster, ELOVL2 and ELOVL5 and fatty acid levels in serum, plasma, red cells, breast milk and adipose tissue [13, 3436]. …”
Section: Genetic Variants: Lcpufa Levels and Human Phenotypesmentioning
confidence: 99%
“…Major allele homozygotes of a 4 SNP haplotype showed more than 3-fold greater apparent conversion of [U- 13 C]-18:3n-3 to [U- 13 C]-20:5n-3 in plasma than minor allele carriers [44]. Al Saleh et al [36] found minor allele carriers of 3 SNP haplotype within the ELOVL2 gene with lower plasma 22:6n-3 than major allele carrier. An SNP within ELOVL5 was nominally associated with decreased capacity to metabolize 20:5n-3 to 22:5n-3 [35].…”
Section: Candidate (Fads Gene Cluster Elovl2 and Elovl5) Gene Studiesmentioning
confidence: 99%
“…GWAS have identified ELOVL2 variants to be associated with serum metabolic profile, aging process and DNA methylation . Recently, ELOVL2 rs3734398 has been reported to be significantly associated with plasma eicosapentaenoic and docosahexaenoic acid proportions after fish oil supplement, which provides evidence on personalized dietary recommendations for reducing cardiovascular disease risk based on the genotype of this SNP . To date, ELOVL2 has not been reported to be associated with CM progression and prognosis.…”
Section: Discussionmentioning
confidence: 99%